Experimental unsteady aerodynamics relevant to insect-inspired flapping-wing micro air vehicles - Phillips, Nathan (Cranfield University, 2011)
Small hand-held micro air vehicles (MAVs) can serve many functions unsuitable for a manned vehicle, and can be inexpensive and easily deployed. MAVs for indoor applications are underdeveloped due to their demanding requirements. Indoor requirements are best met by a flapping-wing micro air vehicle (FMAV) based on insect-like flapping-wing flight, which offers abilities of sustained hover, aerial agility, and energy efficiency. FMAV development is hampered by a lack of understanding of insect-like flapping-wing aerodynamics, particularly at the FMAV scale. An experimental programme at the FMAV scale (Reynolds number on the order of 104) was undertaken, investigating: leading-edge vortex (LEV) stability, flapping kinematic effects on lift and the flowfield, and wing planform shape effects on the flowfield. For these experiments, an apparatus employing a novel flapping mechanism was developed, which achieved variable three-degreeof- freedom insect-like wing motions (flapping kinematics) with a high degree of repeatability in air up to a 20Hz flapping frequency. Mean lift measurements and spatially dense volumetric flowfield measurements using stereoscopic particle image velocimetry (PIV) were performed while various flapping kinematic parameters and wing planform were altered, to observe their effects. Three-dimensional vortex axis trajectories were reconstructed, revealing vortex characteristics such as axial velocity and vorticity, and flow evolution patterns. The first key result was the observation of a stable LEV at the FMAV scale which contributed to half of the mean lift. The LEV exhibited vortex breakdown, but still augmented lift as Reynolds number was increased indicating that FMAVs can exploit this lifting mechanism. The second key result was the identification of the trends of mean lift versus the tested kinematic parameters at the FMAV scale, and appropriate values for FMAV design. Appropriate values for lift generation, while taking mechanical practicalities into account, included a flat wingtip trajectory with zero plunge amplitude, angle of attack at mid-stroke of 45 degrees , rotation phase of +5:5%, and maximum flapping frequency and stroke amplitude.